2021
DOI: 10.1111/pbr.12938
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis of agronomical and physiological traits linked to drought tolerance in a diverse potatoes (Solanum tuberosum) panel

Abstract: Potatoes is often considered a drought‐sensitive crop and its sustainable production is threatened due to frequent drought episodes. Drought tolerance is a complex trait of increasing importance in potatoes therefore its yield is threatened. The differential response of several physiological and agronomical traits was evaluated in a diverse potatoes panel under contrasting water regimes to identify quantitative trait loci (QTL) associated with drought tolerance using genome‐wide association analysis with 4859 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…According to the estimations of LD value, chromosomes 8, 10, and 11 had the highest correlation values between markers, which translates into a greater degree of association between them. High correlation values on chromosome 8 have already been reported by other authors (Berdugo‐Cely et al., 2017; Sharma et al., 2018; Tagliotti et al., 2021; Vos et al., 2015). All of them suggest that chromosome 8 has undergone low selection pressure.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…According to the estimations of LD value, chromosomes 8, 10, and 11 had the highest correlation values between markers, which translates into a greater degree of association between them. High correlation values on chromosome 8 have already been reported by other authors (Berdugo‐Cely et al., 2017; Sharma et al., 2018; Tagliotti et al., 2021; Vos et al., 2015). All of them suggest that chromosome 8 has undergone low selection pressure.…”
Section: Discussionsupporting
confidence: 64%
“…Some results present in the literature seems to indicate the potential of this methodology in potato breeding programs. It has helped to identify markers associated with quantitative traits in tetraploid potato populations (Berdugo‐Cely et al., 2017; D'hoop, 2009; Fischer et al., 2013; Gebhardt et al., 2004; Li et al., 2008; Myles et al, 2009; Malosetti et al., 2007; Simko et al., 2004; Tagliotti et al., 2021; Yousaf et al., 2021). In addition, the association mapping and linkage disequilibrium analysis has been proposed to detect QTL of agronomic interest in other crops with complex inheritance (Basile et al., 2019; Li et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have previously reported QTLs and genomic regions associated with chlorophyll content, chlorophyll fluorescence and NDVI in water stress assays in other populations, indicating that these results are robust [ 71 , 72 , 73 ]. For yield-related parameters, we found markers related to yield, tuber number and reducing sugar content as in previous studies reporting QTLs associated with these traits [ 74 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 63%
“…The soil water content of each pot was determined at 9 a.m. every morning using the gravimetric method described by Martin Enrique Tagliotti et. al [28], and replenished water according to the target soil water content. Sampling was performed after 0, 7, 14, and 21 days of drought treatment.…”
Section: Drought Treatment and Samplingmentioning
confidence: 99%